Knowledge Mapping of Digital Leadership and Research Agenda: The Open Knowledge Maps Perspective - Zam, Efvy Zamidra; Amin, Shofia; Johannes, Johannes; Rosita, Sry (Journal of Applied Data Sciences, 2024)
In today's technological era, digital leadership is necessary for organizational success in facing environmental and technological alteration. This study aims to map digital leadership research using the Open Knowledge Maps platform to find and build cluster visualizations. Moreover, using Open Knowledge Maps as a research analysis tool is rare. The data used is a research paper from 2015-2024 with high metadata quality. This study found 15 clusters related to digital leadership, and most research on digital leadership is carried out in the education field. In addition, this digital leadership study also searches for its effect on employee performance. This study implies that it can find research gaps that can be helpful for future research as the basis for further research.